2008
DOI: 10.1029/2008gc001983
|View full text |Cite
|
Sign up to set email alerts
|

Flank collapse and large‐scale landsliding in the Cape Verde Islands, off West Africa

Abstract: Large‐scale landslides occur on the flanks of many volcanic oceanic islands worldwide. None have taken place in historical time, but their geohazard potential, especially their ability to generate tsunamis, is large. The Cape Verde Islands are a group of 10 large and several smaller volcanic islands off the coast of West Africa between 15 and 17°N. A single flank landslide has previously been described from the island of Fogo, but systematic analysis of the Cape Verde group has until now been lacking. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 36 publications
3
110
0
6
Order By: Relevance
“…According to the methods that these authors applied to the Canary Islands, in the case of Cape Verde, a young island such as Fogo should lack platform as it really occurs (Masson et al, 2008) whereas Boa Vista, with a shelf between 6 and 14 km wide, would have an age be tween 9 and 20 Ma, an idea in agreement with the radiometric age data.…”
Section: Evolution Of the Volcanic Activity Of Boa Vistasupporting
confidence: 67%
See 2 more Smart Citations
“…According to the methods that these authors applied to the Canary Islands, in the case of Cape Verde, a young island such as Fogo should lack platform as it really occurs (Masson et al, 2008) whereas Boa Vista, with a shelf between 6 and 14 km wide, would have an age be tween 9 and 20 Ma, an idea in agreement with the radiometric age data.…”
Section: Evolution Of the Volcanic Activity Of Boa Vistasupporting
confidence: 67%
“…An alternative interpretation is that the depression had formed as a result of a slide, a common event that occurred in other islands of Cape Verde, in Fogo, Santo Antao, Sao Nicolau or Sao Vicente (Elsworth and Day et al, 1999;Le Bas et al, 2007;Masson et al, 2008;Ancochea et al, 2010). The mass-wasting event could account for the absence of trachytes and phonolites or other volcanic rock reliefs in the western sector of the island (Fig.…”
Section: A)mentioning
confidence: 99%
See 1 more Smart Citation
“…2). In addition to onshore evidence for the lateral collapse (Day et al, 1999), Masson et al (2008) reported results of a multibeam bathymetric survey to the east of Fogo, which were interpreted as the avalanche debris of the lateral collapse. Foeken et al (2009) Day et al (1999) and Fonseca et al (2003).…”
Section: Fogo Islandmentioning
confidence: 99%
“…The Planalto Norte plateau was built by the infilling with young volcanic rocks of two escarpments opened to the southwest, which Tarff and Day (2013) attribute to two successive lateral collapses. Masson et al (2008) used multibeam and acoustic backscatter images to map areas of blocky bathymetry offshore of the island, which they interpreted as two different submarine debris avalanche deposits originating from Topo de Coroa. Airfall pumice deposits of phonolitic composition are found almost everywhere on the island, but are especially thick (up to 8 m) on the Planalto Norte.…”
Section: Santo Antãomentioning
confidence: 99%